2022
DOI: 10.1002/lpor.202270056
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Applications of Nanomaterials for Ultrafast Photonics (Laser Photonics Rev. 16(11)/2022)

Abstract: Ultrafast Photonics Nanomaterials with remarkable optical properties including carbon‐based, typical two‐dimensional, and metal‐based nanomaterials have been widely used in ultrafast photonics over the years. In article number 2200386, Bo Fu, Han Zhang, and co‐workers review the ultrafast applications, typical parameters of ultrafast lasers, features of each nanomaterial, and further development in ultrafast photonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The D-shaped fibers have a thick core, so it has good robustness. High-quality D-shaped fibers can be obtained by simple polishing techniques, but this also leads to more polarizationdependent loss [52,53]. Tapered fibers avoid this drawback by controlling the length of the tapered melt zone to modify the nonlinear absorption effect.…”
Section: Evanescent Field Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The D-shaped fibers have a thick core, so it has good robustness. High-quality D-shaped fibers can be obtained by simple polishing techniques, but this also leads to more polarizationdependent loss [52,53]. Tapered fibers avoid this drawback by controlling the length of the tapered melt zone to modify the nonlinear absorption effect.…”
Section: Evanescent Field Interactionmentioning
confidence: 99%
“…Some nanomaterials have the advantages of nonlinear optical properties and fast response time, qualifying themselves as excellent SAs in lasers. As an alternative to artificial SAs such as the SESAM, nanomaterials as real SAs have wider bandwidth and lower manufacturing cost [53,54]. Therefore, an increasing number of tunable lasers reported in the past few years adopted nanomaterials as SAs to achieve passively mode-locked pulses.…”
Section: Applications Of Nanomaterials In Wavelengthtunable Broadband...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vicario, C et al groups investigated the high-field THz generation in organic crystals DSTMS, DAST, and OH1 by optical rectification process using femtosecond Cr: fosterite laser pulse at 10 Hz repetition and they have achieved maximum conversion efficiency as high as 3% which corresponds to energy per pulse up to 270 μJ [15]. Whereas, Zhang B et al reported highest energy of the order of 1.4 mJ terahertz radiation from a Lithium Niobates crystal [16]. In addition, GaSe which is one of the oldest nonlinear single crystal and attracted researchers for improvising its optical and surface hardness properties using different types of dopants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dielectric property of GaSe: S was measured using time-domain THz spectroscopy [18,19]. The GaSe:S can be treated as one of the suitable alternatives of LiNbO 3 and ZnTe crystals for the generation of THz radiation in the laboratory [16,31]. The first one is used for strong THz generation but possesses big difference between their optical and THz refractive indices which drastically reduces the coherence length of the LiNbO 3 and not preferred for the detection purpose.…”
Section: Introductionmentioning
confidence: 99%